2015
DOI: 10.1002/celc.201500052
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Chromium Substitution in Na3V2(PO4)3 as a Potential Candidate for Sodium‐Ion Batteries

Abstract: The effect of low‐level chromium substitution in Na3V2‐xCrx(PO4)3 (0≤x≤0.4), a potential cathode material in Na‐ion cells, has been examined. A suitable synthesis procedure is developed to obtain composites of crystalline NASICON phosphate and an amorphous carbon phase to enhance the electrical conductivity of the electrode. The optimized cathode materials were characterized by using X‐ray diffraction and spectroscopic techniques. The electrochemical evaluation was carried out by using galvanostatic and potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
79
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(86 citation statements)
references
References 43 publications
(1 reference statement)
7
79
0
Order By: Relevance
“…[30,31] It is commonly reported that the I G /I D1 ratio is am easureo ft he level of graphitization of the carbon material. [16,37,38] On increasing the Cr ate from C/2 to 40 C, ad ecrease in capacity is clearlyo bserved as expected from the fast kinetics which are imposed at the highest rate. Figure 6d isplays the charge and dischargec urves recorded on sodium half-cells assembled witht he studied samples as workinge lectrodes.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…[30,31] It is commonly reported that the I G /I D1 ratio is am easureo ft he level of graphitization of the carbon material. [16,37,38] On increasing the Cr ate from C/2 to 40 C, ad ecrease in capacity is clearlyo bserved as expected from the fast kinetics which are imposed at the highest rate. Figure 6d isplays the charge and dischargec urves recorded on sodium half-cells assembled witht he studied samples as workinge lectrodes.…”
Section: Resultsmentioning
confidence: 79%
“…The quantitative analysis showed ag ood agreement between the actual composition and their theoretical values (Table S2). [16] For NVP-0.1, small and dark nanosized particlesa ppear neart he Na 3 V 2 (PO 4 ) 3 surface (marked with arrows). These values are close to the stoichiometric ones.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7] On the other hand, the applications of PBAs are limited by their low volume density, inferior thermal stability, and toxicity of cyanide. Lavela and co-workers used Cr to replace 10% of V and the as-synthesized Na 3 V 1.8 Cr 0.2 (PO 4 ) 3 showed a short plateau above 3.8 V. [24] This high-potential plateau can be prolonged by increasing the amount of Cr to 50%, forming a new material Na 3 VCr(PO 4 ) 3 , which has been reported by Yang and co-workers. [11][12][13] Recently, the Na superionic conductor (NASICON)-structured polyanion-type materials are of significant interest because of their unique crystal framework that is constructed by units of MO 6 octahedrons (M represents transition metals) and XO 4 tetrahedrons (X = P, S, Si, As), building 3D ion channels for fast Na + migration.…”
mentioning
confidence: 55%
“…[15,16] The V 4 + /V 3 + and Ti 4 + /Ti 3 + redox processes in vanadium-and titanium-based insertion hosts with the NASI-CON structure occur within the electrochemical stability window of water. [20][21][22][23][24][25] In consequence,a mphoteric insertion hosts that can be used as cathode and anode materials are being developed. Specifically,N aTi 2 (PO 4 ) 3 is of high interest because it is redox active at the lower end of the aqueous electrolyte stabilityw indow,w hicht hus enables enhanced energy densities.…”
Section: Introductionmentioning
confidence: 99%